Analysis of Output Characteristics of Electrically Excited Doubly Salient Generator Based on Back EMF Oriented Vector Control Strategy - Weifeng Liu; Yulong Tao; Xiaoli Meng (IEEE Access)
Compared to using uncontrolled rectifier, the use of active rectifier can significantly improve the output power of doubly salient electric generator (DSEG). The traditional six-state-angle-control (SSAC) strategy has limited effectiveness in improving the output power of DSEG. A mathematical model of DSEG in a rotating coordinate system oriented by back electromotive force (EMF) vector was established based on the principle of instantaneous reactive power. The reason why SSAC strategy is difficult to further improve the output power of DSEG was analyzed through this model. To address this issue, this paper proposed a back EMF oriented vector control (BEFOVC) strategy. Compared with SSAC strategy, BEFOVC can further optimize the output performance of DSEG, reduce copper loss, phase current peak and THD, and suppress the torque ripple of DSEG. Finally, the feasibility and effectiveness of the proposed method were verified through simulations and experiments on a 12/8-pole DSEG.